Enacting Change: A Study of the Implementation of e-Readers and an Online Library in two Canadian High School Classrooms - Patterson, Serina; Stokes-Bennett, Devon; Siemens, Ray; Nahachewsky, James (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
In this paper the authors discuss their interdisciplinary pilot project entitled ‘Teaching for the 21st Century: A Pilot Project on E-Reading with SD62’ that engaged in the development and implementation of a customized and purpose-specific online library for two selected high school classrooms at a time when such systems did not exist for this purpose. This project combined (1) information literacy issues, (2) pedagogy and e-pedagogy, and (3) computational modeling activities founded on a productive confluence of these perspectives all situated at the intersection of pertinent theories and practices pertaining to each. The result of the research project was a functional online library environment that worked in the classrooms to support born-digital students' engagement with e-readers and findings of the way in which these both worked in the context of multiliteracies classrooms.